Clinical practice pattern in patients with advanced urothelial cancer who had progressed on pembrolizumab in the pre‐enfortumab vedotin era. (18th March 2022) - Kita, Yuki; Ito, Katsuhiro; Sano, Tomoyasu; Hashimoto, Kohei; Mochizuki, Takanori; Shiraishi, Yusuke; Araki, Hiromasa; Fujiwara, Maki; Kanamaru, Sojun; Takahashi, Takehiro; Hishiki, Kosuke; Okada, Takuya; et al.
Abstract : Objectives: Pembrolizumab, an anti‐PD‐1 monoclonal antibody, revolutionized the treatment for advanced urothelial carcinoma. However, the standard treatment for patients after disease progression with pembrolizumab had not been established until the recent approval of enfortumab vedotin. We analyzed the treatment of these patients in the real world, and the patient background and outcomes. Methods: We extracted data from 543 patients who experienced progressive disease after pembrolizumab initiation from a Japanese nation‐wide cohort of platinum‐refractory, metastatic urothelial carcinoma. Results: The median overall survival of the 543 patients was 3.5 months (95% confidence interval 3.0–4.1). Of these, only 20.6% ( n = 112) received chemotherapy as a subsequent systemic treatment after progressive disease. The regimen of chemotherapy was very diverse. The median overall survival was 11.9 months (95% confidence interval 9.2–14.7) for patients who received chemotherapy, compared to 2.4 months for those who did not receive chemotherapy (95% confidence interval 2.1–2.9; P < 0.0001). Patients who received subsequent chemotherapy were more likely to have better performance status, neutrophil‐to‐lymphocyte ratio <3, hemoglobin >11 mg/dL, and history of a single chemotherapeutic regimen at pembrolizumab initiation. Conclusions: This report highlights the real‐world practice of the management after pembrolizumab treatment failure in the pre‐enfortumab vedotin era, characterized by infrequent use of subsequent anticancer therapy comprising various regimens, reflecting the lack of a standard treatment. Clinical introduction of enfortumab vedotin is expected to improve treatment outcomes in this setting. The present study will provide important baseline data for evaluating the influence of enfortumab vedotin on clinical practices and outcomes.